2005
DOI: 10.1002/eji.200526042
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor immune response by CX3CL1 fractalkine gene transfer depends on both NK and T cells

Abstract: The CX3C chemokine fractalkine (CX3CL1) exists as both a membrane-bound form promoting firm cell-cell adhesion and a soluble form chemoattracting leukocytes expressing its receptor CX3CR1. When adenoviral vector expressing mouse fractalkine (AdFKN) was transduced to the tumor cells, fractalkine was expressed as both membrane-bound form on the tumor cells and soluble form in the supernatant in vitro. Intratumoral injection of AdFKN (1Â10 9 PFU/tumor) into C26 and B16F10 tumors resulted in marked reduction of tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
83
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(90 citation statements)
references
References 39 publications
6
83
1
Order By: Relevance
“…Although the mechanisms by which fractalkine exerts its antitumor activity on osteosarcoma lung lesions have not been identified yet, we can suppose that innate immunity (via NK cells) and adaptive immunity (via CD8 þ T cells and/or dendritic cell) are likely to play a major role in mediating tumor regression of osteosarcoma lung metastasis as reported in colon carcinoma and in many other solid tumors development. [8][9][10][11]13,30,31 In addition to reinforcing this assumption, IL-12, which notably activates NK cells and facilitates the induction of cytotoxic and T helper type 1 T cells, [32][33][34][35] was found to inhibit the development of osteosarcoma lung metastases.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Although the mechanisms by which fractalkine exerts its antitumor activity on osteosarcoma lung lesions have not been identified yet, we can suppose that innate immunity (via NK cells) and adaptive immunity (via CD8 þ T cells and/or dendritic cell) are likely to play a major role in mediating tumor regression of osteosarcoma lung metastasis as reported in colon carcinoma and in many other solid tumors development. [8][9][10][11]13,30,31 In addition to reinforcing this assumption, IL-12, which notably activates NK cells and facilitates the induction of cytotoxic and T helper type 1 T cells, [32][33][34][35] was found to inhibit the development of osteosarcoma lung metastases.…”
Section: Discussionmentioning
confidence: 93%
“…In the context of chemokinetransduced tumor cells, the overexpression of fractalkine in various experimental tumor models has been shown to promote a tumor-suppressive activity by improving the recruitment of distinct leukocytes depending on the tumor type. [8][9][10][11][12][13][14] Of interest, our group has demonstrated the T-cell-mediated immunotherapeutic potential of constitutive fractalkine expression by colon carcinoma cells. 13 More recently, mesenchymal stem cells have been used to deliver fractalkine into lung metastases of C26, Lewis lung carcinoma or B16F10 tumor mice, and resulted in a strong antitumoral effect and prolonged survival in mice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,29 Murine colon adenocarcinoma cells C26 and melanoma B16F10 cells showed that antitumor immune response induced by FK gene transfer depended on NK and T cells. 30 However, Lavergne et al 31 reported that in the EL-4 lymphoma model, FK-mediated antitumor effects occurred only via NK cells but not T cells because this antitumor effect was observed only in T cell-and B cell-deficient Rag1-/-mice, but was ablated in NK Antitumor effect of fractalkine in liver cancer L Tang et al cell-deficient beige mice. Another study showed that no significant antitumor effect of FK was found when using an ex vivo gene transfer into OVHM tumor cells by an adenoviral vector.…”
Section: Discussionmentioning
confidence: 99%
“…This chemokine is critically important for infiltration (chemotaxis and adhesion) of various lineages of lymphocytes characterized by a high content of intracellular perforin and granzyme, and monocytes/macrophages expressing its receptor Endocrine-Related Cancer (2009) 16 211-224 www.endocrinology-journals.org CX3CR1 in human carcinomas (Guo et al 2003, Ohta et al 2005. Previous reports have demonstrated that the antitumor effects elicited by fractalkine gene transfer into subcutaneously implanted murine cancer cell lines depend on NK and T cells (Guo et al 2003, Lavergne et al 2003, Xin et al 2005. Consistent with our data, high endogenous fractalkine expression in neuroblastoma (Zeng et al 2007), colorectal cancer (Ohta et al 2005), and gastric adenocarcinoma (Hyakudomi et al 2008), where it is mainly observed in the plasma membrane and cytoplasm of tumor cells, correlated with a higher density of tumor-infiltrating immune cells.…”
Section: Dysregulation Of Host Antitumor Response Mechanisms During Rmentioning
confidence: 99%